Study on mechanical properties and ratio parameter optimization of fly ash wet shotcrete under the influence of multiple factors - Xionggang Zou; Yaoping Zhang; Bo Liu; Xinmu Xu; Zhigang Lu; Wenwu Jiang (Case Studies in Construction Materials, 2023)
In order to eliminate the large amount of waste rock and tailings deposited on the surface, waste rock tailings are used as aggregate to prepare wet shotcrete, and fly ash is added instead of cement to reduce the cost. Based on the orthogonal test system, the effects of cement content, mass concentration, waste rock content and fly ash content on the strength and slump of wet shotcrete were analyzed, and the ratio parameters were optimized. The results show that the compressive strength of wet shotcrete increases with longer curing time, yet the rate of strength increase diminishes with prolonged curing time. For slump of slurry, mass concentration and waste rock content are the two factors with the highest degree of influence, which are significant factors. Regarding the compressive strength and tensile strength indexes, the most influential factors are found to be the mass concentration and cement content, both of which demonstrate a substantial impact. The strength and slump are not only affected by a single factor, but also by the interaction between the factors. The optimal design parameters obtained by multi-objective optimization are as follows: cement content of 290 kg/m3, mass concentration of 79%, Waste rock content of 70%, fly ash content of 16%. The increase of cement content and mass concentration will reduce the formation of void structure in the sample and enhance its macroscopic mechanical properties.